Interfraction Motion of the Vaginal Apex During Postoperative Intensity Modulated Radiation Therapy: Are We Missing the Target?. Issue 2 (1st February 2013) - Rash, Dominique; Hagar, Yolanda; Cui, Jing; Hunt, Jon-Paul; Valicenti, Richard; Mayadev, Jyoti
Abstract : Objective: This study aimed to evaluate changes in vaginal cuff position and rectal distention during whole pelvic intensity modulated radiation therapy using daily image guidance for patients with gynecologic malignancies. Materials and Methods: We reviewed 145 daily images from 5 patients treated with intensity modulated radiation therapy after total abdominal hysterectomy for endometrial or cervical cancer. A fiducial marker was placed in the vaginal cuff tissue before computed tomographic simulation. The 2008 ASTRO consensus guidelines for delineation of clinical target volumes were used to deliver 45 to 50 Gy to the target structures. Daily megavoltage computed tomographic images were reviewed and changes in position of the fiducial marker as compared to the initial planning scan were recorded in the anterior-posterior (AP), lateral, and superior-inferior dimensions. Changes in rectal distention were also recorded. The position of the fiducial marker relative to the planning target volumes was reviewed on each daily image. Results: The average shifts of the gold seed in the AP, lateral, and superior-inferior dimensions were 7 mm (range, 0–28 mm), 3 mm (range, 0–7 mm), and 2.9 mm (range, 0–12 mm), respectively. Distention of the rectum ranged from 20.5 to 60.1 mm and correlated with movement of the gold seed in the AP dimension ( R = 0.53). For 2 patients, the fiducial marker was within 5 mm of the planning target volume margin on 8/40 treatments, or outside the planning target volume on 4/40 treatments. This did not significantly impact total delivered dose to the planning target volume. Conclusions: Daily image guidance confirms significant interfraction movement of the vaginal cuff tissue, which may exceed suggested guidelines for clinical target volume margins.